2013
DOI: 10.1021/la400561t
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Dissociation from Crocidolite Asbestos Acts as Persistent Signal for Epidermal Growth Factor Receptor

Abstract: Mesothelioma is an incurable form of cancer located most commonly in the pleural lining of the lungs and is associated almost exclusively with the inhalation of asbestos. The binding of asbestos to epidermal growth factor receptor (EGFR), a transmembrane signal protein, has been proposed as a trigger for downstream signaling of kinases and expression of genes involved in cell proliferation and inhibition of apoptosis. Here, we investigate the molecular binding of EGFR to crocidolite (blue asbestos; Na2(Fe(2+),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Currently, no data is available on how CNT could interact with these receptors. Asbestos fibers have been shown to directly bind and activate EGF receptor [ 35 ], suggesting that CNT could somehow interact with kinase receptors. Azad et al [ 14 ] and Vietti et al [ 34 ] have identified different mechanisms leading to CNT-induced fibroblast proliferation.…”
Section: The Direct Effects Of Cnt On Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, no data is available on how CNT could interact with these receptors. Asbestos fibers have been shown to directly bind and activate EGF receptor [ 35 ], suggesting that CNT could somehow interact with kinase receptors. Azad et al [ 14 ] and Vietti et al [ 34 ] have identified different mechanisms leading to CNT-induced fibroblast proliferation.…”
Section: The Direct Effects Of Cnt On Fibroblastsmentioning
confidence: 99%
“…MWCNT (25–100 μg/ml) were shown to induce the release of IL-1β and IL-18 by cultured alveolar macrophages isolated from naive C57BL/6 mice and by human monocytic cell line (THP-1), and their secretion was suppressed by inhibitors of caspase-1 and cathepsin B [ 42 ]. Several other in vitro studies observed that CNT enhanced IL-1β release in macrophages via inflammasome activation, nuclear factor-kappa B (NF-kB) and oxidative stress [ 13 , 35 , 36 , 43 47 ], which we discuss in the mechanisms section. Moreover, IL-1β has also been shown to induce the release of the pro-fibrotic mediators TGF-β and PDGF from different cell types, thus highlighting the importance of the pro-inflammatory mediators released by macrophages [ 13 ].…”
Section: Indirect Effects Of Cnt On Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also be associated with oncogenesis (e.g., mesothelioma) through aberrant activation of the cell signaling cascades. A part of this signaling cascade is the activation of EGFR through binding of either biological compounds, such as extracellular ligands (i.e., EGF), or foreign substances . Upon binding to a ligand, the receptor homo‐ or heterodimerizes and autophosphorylation start the signal to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…NF B role in MWCNT molecular mechanism of toxicity has been extensively studied and is well accepted [96] . Similarly, IL-17 mediates protective innate immunity mechanisms against a plethora of pathogens, and is nowadays regarded a potential pivotal therapeutical target in inflammation pathogenesis [97] , [98] , [99] , [100] , [101] , [102] .
Fig.
…”
Section: Use Of the Nextcast Componentsmentioning
confidence: 99%